Total Phenolic Content and Antioxidant Activity of Pasteurized Milk With the Addition of Centella asiatica Leaf Extract - Distya Riski Hapsari; Intan Kusumaningrum; Arti Hastuti; Caesandra Indah Arlina; Lia Amelia (Universitas Djuanda, 2023)
Milk has a high nutritional value. Minimal processing that can extend the shelf life of milk is pasteurization, but it can damage the nutritional content of milk. One of the additional efforts to improve milk quality and maintain the nutritional content of milk is to provide additional active compounds that act as antioxidants for milk consumers and the milk product itself. The use of Centella asiatica leaf extract as an ingredient is because there are at least 139 active compounds. This study aimed to study the total phenolic content and antioxidant activity of pasteurized milk with the addition of Centella asiatica leaf extract. The research was carried out in two stages, namely making gotu kola leaf extract and making pasteurized milk by adding gotu kola leaf extract concentrations of 0%, 0.25%, 0.5%, and 0.75%. Product analysis included total phenol analysis using Folin Ciocalteau and antioxidant activity using the DPPH method. Adding Centella asiatica leaf extract can increase total phenolic content and antioxidant activity. The total phenolic content obtained by adding Centella asiatica leaf extract at 0%, 0.25%, 0.50%, and 0.75% were 0.58 mgGAE/g, 1.93 mgGAE/g, respectively 2.33 mgGAE/g, and 3.41 mgGAE/g. At the same time, the results of antioxidant activity were 7.68%, 31.93%, 37.57, and 40.35%, respectively.